Dipole effects on the formation of molecular junctions. Issue 5 (9th June 2016) - Tanimoto, Sachie; Tsutsui, Makusu; Yokota, Kazumichi; Taniguchi, Masateru
Abstract : Measuring the tunneling current is a promising way of identifying individual molecules in a liquid, wherein the electric field in an electrode gap plays an important role on restricting the conformational degrees of freedom through electrostatic interactions with the molecular dipoles. Abstract : Measuring the tunnelling current is a promising way of identifying individual molecules in a liquid, wherein molecular conformations in an electrode gap play a crucial role in the electron transport properties. Here we report that molecular dipole interactions with the electric field effectively restrict the configurational degrees of freedom in metal–molecule–metal systems. We utilized a mechanically tunable Au nanoelectrode gap to electrically detect diaminobenzene isomers. We found suppression of a variation in the single-molecule conductance of 1, 2-benzenediamines (BDAs) in water suggesting a significant influence of the huge electric field created between the nanoprobes to align the molecular dipole along the potential gradient and concomitant formation of well-defined junction structures for the molecules through-space coupled to one side of the electrodes. On the other hand, the field effect was absent in 1, 3- and 1, 4-BDAs, which is attributed to their smaller dipole moments and the more rigid chemical connections to the electrodes via Au–amine bonds.